Second Relapse of Pediatric Patients with Acute Myeloid Leukemia: A Report on Current Treatment Strategies and Outcome of the AML-BFM Study Group - Rasche, Mareike; Steidel, Emma; Zimmermann, Martin; Bourquin, Jean-Pierre; Boztug, Heidrun; Janotova, Iveta; Kolb, E Anders; Lehrnbecher, Thomas; von Neuhoff, Nils; Niktoreh, Naghmeh; Mühlegger, Nora; Sramkova, Lucie; et al. (Cancers, 2021)
Successful management of relapse is critical to improve outcomes of children with acute myeloid leukemia (AML). We evaluated response, survival and prognostic factors after a second relapse of AML. Among 1222 pediatric patients of the population-based AML-Berlin-Frankfurt-Munster (BFM) study group (2004 until 2017), 73 patients met the quality parameters for inclusion in this study. Central review of source documentation warranted the accuracy of reported data. Treatment approaches included palliation in 17 patients (23%), intensive therapy with curative intent (n = 46, 63%) and other regimens (n = 10). Twenty-five patients (35%) received hematopoietic stem cell transplantation (HSCT), 21 of whom (88%) had a prior HSCT. Survival was poor, with a five-year probability of overall survival (pOS) of 15 ± 4% and 31 ± 9% following HSCT (n = 25). Early second relapse (within one year after first relapse) was associated with dismal outcome (pOS 2 ± 2%, n = 44 vs. 33 ± 9%, n = 29; p < 0.0001). A third complete remission (CR) is required for survival: 31% (n = 14) of patients with intensive treatment achieved a third CR with a pOS of 36 ± 13%, while 28 patients (62%) were non-responders (pOS 7 ± 5%). In conclusion, survival is poor but possible, particularly after a late second relapse and an intensive chemotherapy followed by HSCT. This analysis provides a baseline for future treatment planning.
Keywords: acute myeloid leukemia; pediatric; relapse; salvage therapy; childhood acute myeloid leukemia